Beneficial effect of botulinum toxin A on Raynaud's phenomenon in Japanese patients with systemic sclerosis: A prospective, case series study. Issue 1 (15th July 2015) - Motegi, Sei‐ichiro; Yamada, Kazuya; Toki, Sayaka; Uchiyama, Akihiko; Kubota, Yuka; Nakamura, Tetsuya; Ishikawa, Osamu
Abstract: Currently, there is no satisfactory treatment for Raynaud's phenomenon (RP) in systemic sclerosis (SSc). Recently, it has been reported that botulinum toxin A (BTX‐A) injection was effective for the treatment of RP in SSc patients. The objective was to assess the efficacy and safety of BTX‐A on RP in Japanese SSc patients. In the prospective, case series study, 10 Japanese SSc patients with RP received 10 U of BTX‐A injections into the hand. The change in severity of RP, including the frequency of attacks/pain, color changes, duration time of RP and the severity of pain, was assessed by Raynaud's score and pain visual analog scale (VAS) at each visit during 16 weeks. The recovery of skin temperature 20 min after cold water stimulation was examined by thermography at baseline and 4 weeks after injection. The number of digital ulcers (DU) and adverse effects were assessed at each visit. BTX‐A injection decreased Raynaud's score and pain VAS from 2 weeks after injection, and the suppressive effect was continued until 16 weeks after injection. Skin temperature recovery after cold water stimulation at 4 weeks after injection was significantly enhanced compared with that before injection. All DU in five patients were healed within 12 weeks after injection. Neither systemic nor local adverse effects were observed in all cases. We conclude that BTX‐A injection significantly improved the activity of RP in SSc patients without any adverse events, suggesting that BTX‐A may have possible long‐term preventive and therapeutic potentials for RP in Japanese SSc patients.